2013
DOI: 10.12938/bmfh.32.149
|View full text |Cite
|
Sign up to set email alerts
|

Slower Fermentation Rate of Potato Starch Relative to High-amylose Cornstarch Contributes to the Higher Proportion of Cecal Butyrate in Rats

Abstract: This study aimed to examine the mechanism for differential effects of low- (LPPS) and high-phosphorus (HPPS) potato starches and high-amylose cornstarch (HACS) on rat cecal fermentation, the n-butyrate proportion in particular. In ileorectostomized rats, the in vivo resistant starch (RS) contents were determined to be 66% (LPPS), 66% (HPPS) and 36% (HACS), but the carbohydrate/nitrogen (C/N) ratios of the ileal digesta were comparable among the respective starch diets. In intact rats fed diets including simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Consumption of HAS and potato starch diets increased acetate and total-SCFA productions and lowered pH in rat cecum similar to previous studies (14,15). However, cecal propionate concentration was not different among the groups in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consumption of HAS and potato starch diets increased acetate and total-SCFA productions and lowered pH in rat cecum similar to previous studies (14,15). However, cecal propionate concentration was not different among the groups in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the effect of raw potato stach on the intestinal fermentation properties in rats were examined. HAS and potato starch isolated from SD and KH contained high RS levels, and the cecal content weights in these groups were higher similar to previous studies (14,15). Further, it has been reported that starch with lower digestibility increases the amount of digesta in the distal gut, and a large volume of digesta is known to provide a favourable environment for microbial growth in the distal gut by providing nutrients to gut bacteria (3,20).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Notably, labeled metabolites for cross-feeding might have also resulted from starch hydrolysis mediated by the host itself in the small intestine through the enzymatic activity of pancreatic α-amylases, mucosal maltase-glucoamylases and sucrose-isomaltases [ 55 ]. However, starch fractions from potatoes were shown to be degraded rather slowly in comparison to other botanical sources in vitro and in vivo [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raw potato starch (PS) is resistant to digestive enzymes and contains a higher RS content. [ 2 ] It has been suggested that the presence of high quality esterified phosphate groups in PS causes the inhibition of hydrolysis by α‐amylase. [ 3,4 ] Consumption of raw PS is reported to promote the production of SCFAs and lower the colonic pH through fermentation by colonic microbiota.…”
Section: Introductionmentioning
confidence: 99%